Yield stability of new elite lines of yardlong bean (Vigna unguiculata (L.) Walp. subsp. sesquipedalis Verdc.) - Pornsuriya, P.; Pornsuriya, P.; Kwun-on, P.; Chittawanij, A. (International Journal of Agricultural Technology, 2021)
The yield trials of new elite lines of yardlong bean under nine environments revealed that they differently responded to multi-environments for horticultural traits and yield. Genotype-environment interactions were significantly found (P < 0.01) for the days of anthesis, pod length, seeds per pod, pod weight and yield per hectare. Significant differences (P < 0.01) of yield were observed for genotypes, environments, and genotype-environment interaction. Stability analysis after Eberhart and Russell’s model suggested that non-linear component was more important than linear component for determining the yield stability. Based on stability parameters, line No.30 was identified as stable for yield since it gave high yield (14.17 t/ha), high positive phenotypic index (Pi > 0), regression coefficient around unity (bi = 1), and deviation from regression value around zero ( = 0). Bangpra2 and No.25 lines also gave high yield but their deviations from regression were highly significant, it clearly shown that these 2 lines were unpredictable expected by linear regression. However, considering their yields from various environments, they were suitable for highly favorable environments but under poor environments. Environmental index which directly reflected the poor and rich environment in terms of negative and positive of yield revealed that environments 1 and 2 were rich environments, and environments 6 and 9 were poor environments.